DANA BAGI HASIL SEKTOR PAJAK ERA OTONOMI DAERAH DI JAWA TENGAH - Sulistyowati, Sulistyowati (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2007)
To archieve vertical equalitation in the level of province in Indonesia there are two types of transfer fund which are extracted from tax and natural resources revenues. This research will focus on the tax-based vertical equalization type of sharing namely land and construction tax (PBB). In Central Java Land and Construction tax increases 20% per annum during the five year under observation. However, due to the absent for any regulation on the allocation of the Land and Construction Tax revenues, the province often allocates the revenue unprudently.